2010
DOI: 10.1149/1.3484764
|View full text |Cite
|
Sign up to set email alerts
|

Process Variables that Control Natural Fiber Welding

Abstract: Preliminary data are shown for a systematic study of the variables that control the fiber welding process. Cotton cloth samples are treated with various amounts of 1-ethyl-3-methylimidazolium acetate for a series of times and temperatures. Processed materials are characterized by scanning electron microscopy, infrared spectroscopy, x-ray diffraction, and mechanical (tensile) testing. Chemical and physical properties are shown to be controllably modified with careful management of process variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…NFW is quite versatile, as any number of ILs can be applied to natural fiber materials including lignocellulose (e.g., cotton, linen, hemp, bamboo) and other biopolymers (e.g., silk, chitin). Additionally, studies have shown that NFW can maintain or improve the mechanical properties of the underlying natural fiber supports, , extending their use to more advanced engineering applications. In previous work, researchers at the U.S.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NFW is quite versatile, as any number of ILs can be applied to natural fiber materials including lignocellulose (e.g., cotton, linen, hemp, bamboo) and other biopolymers (e.g., silk, chitin). Additionally, studies have shown that NFW can maintain or improve the mechanical properties of the underlying natural fiber supports, , extending their use to more advanced engineering applications. In previous work, researchers at the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…24 Padalkar et al developed nanofabrication techniques to control and optimize monometallic nanoparticle deposition onto cellulose nanocrystals. 25 A distinct advantage of lignocellulose over conventional catalyst supports is that it can be postprocessed through natural fiber welding (NFW) 26 into free-standing structures. In NFW, lignocellulose fibers are partially dissolved and mobilized upon exposure to controlled amounts of ionic liquid (IL), then reorganized upon IL removal.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mobility to interact more intimately with adjacent fibers. 748 As far as cellulose fibers, while one may expect individual fibers to be weakened due to the conversion of highly crystalline cellulose I into less ordered cellulose II, the structural integrity of the fibrous network is likely to be improved through more extensive interactions, leading to reinforced materials. Indeed, ionic liquid-welded, hot-pressed CNF films were found to be surface patterned, more transparent, stiffer and tougher than the untreated film.…”
Section: Avmentioning
confidence: 99%
“…738 The welding extent is controlled primarily by the temperature (controls mostly swelling and dissolution rates), time (controls mainly penetration depth and net dissolution extent) and pressure plus the characteristics of the solvent itself, such as chemical nature and concentration. 748,750 Besides spinning or extruding biopolymeric dopes and inducing alignment, for example, into yarns, anisotropy is achievable by restricting the macromolecular rearrangement when drying stresses are developed upon solvent removal. This is the case of cellulose or alginate physical gels that are air-dried under confinement in the axial direction.…”
Section: Avmentioning
confidence: 99%